Microarray Analysis of Quorum-Sensing-Regulated Genes in Porphyromonas gingivalis - Yuan, Lihui (American Society for Microbiology, 2005)
Quorum sensing is a phenomenon defined as gene regulation in response to cell density that regulates various functions in bacteria. The periodontopathogen Porphyromonas gingivalis possesses a luxS gene homologue that may encode a quorum-sensing system. In order to identify genes of P. gingivalis that are regulated by luxS, gene expression analysis was done using microarrays and RNA samples from the W83 wild-type strain and an isogenic luxS mutant, LY2001. The results indicated that 17 open reading frames (ORFs) in LY2001 are upregulated and two are downregulated. Real-time PCR was done to confirm the microarray results. Among the upregulated ORFs is a group of stress-related genes, including htrA, clpB, groEL, dnaK, and the F subunit of alkyl hydroperoxide reductase. This suggested that luxS is involved in stress gene regulation in P. gingivalis. Stress response experiments, including high-temperature survival, resistance to hydrogen peroxide (H(2)O(2)), and survival during exposure to low and high pH, were performed on the P. gingivalis wild-type and LY2001 strains. LY2001 had a significantly higher survival rate than did W83 when stressed at 50°C. No difference was found at pH 5, but LY2001 had increased survival compared to W83 at pH 9. LY2001 also survived better than W83 when stressed with 0.35 mM H(2)O(2). These results suggest that luxS might be involved in promoting survival of P. gingivalis in the host by regulating its response to host-induced stresses such as temperature, H(2)O(2), and pH.